Socialization of Waste Handling Using the Concept of Reduce, Reuse, Recycle and Replace (4 R) to the Community in Kastela Village - Marwan, Marwan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Waste is the residue of various human activities, both in the form of consumption and development activities. The purpose of this activity is to educate the community in order to be able to handling of these residual materials so as to reduce the negative its negative impact, both on society and the environment. This activityThis activity was carried out by counselling a group of people by presenting various practices on how to handle waste that have been done in many places, known as in various places, which is known as the concept of the 4 R's, namely reduce, reuse, recycle, and replace.